2015
DOI: 10.3109/07420528.2015.1064130
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the cortisol-awakening response during the first two years of shift work: A longitudinal study in novice police officers

Abstract: Cortisol acts as a critical biological intermediary through which chronic stressors like shift work impact upon multiple physiological, neuro-endocrine and hormonal functions. Therefore, the cortisol awakening response (CAR) is suggested as a prime index of shift work tolerance. Repeated assessments of the CAR (calculated as MnInc) in a group of 25 young novice police officers showed that in the interval between about 4 and 14 months after transitioning from regular day work to rotating shift work, mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Furthermore, we recruited relatively larger sample size empowering our ability to detect fairly modest associations with statistical significance compared to most of earlier studies. To our knowledge, our study also produced first evidence of a longitudinal link between shift work and the cortisol slope, in addition to existing longitudinal findings on waking cortisol and total cortisol AUC [ 43 , 44 ]. Nevertheless, our study also suffered several limitations.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, we recruited relatively larger sample size empowering our ability to detect fairly modest associations with statistical significance compared to most of earlier studies. To our knowledge, our study also produced first evidence of a longitudinal link between shift work and the cortisol slope, in addition to existing longitudinal findings on waking cortisol and total cortisol AUC [ 43 , 44 ]. Nevertheless, our study also suffered several limitations.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, the three longitudinal studies in the past decade deserve a close look. The Dutch study found an increase in waking salivary cortisol when police officers commenced duty of shift work 1 year later, and the effect was maintained for almost 2 years [ 44 ], while the German study, among industrial workers, suggested more cortisol secretion in saliva as larger AUC by changing work schedule from day shift to night shift for 2 months [ 43 ]. However, these two studies did not set an external reference group, that is, pre-and-post comparisons were actually conducted within subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shift work exerts influence on multiple physiological, neuroendocrine, and hormonal functions. As a result, CAR is currently considered to be a major index of shift work tolerance [27]. Research has shown that changes in CAR may be the result of increased stress and impaired sleep quality following shift changes; however, controlling for shift factor revealed no significant differences in CAR variations [28].…”
Section: Discussionmentioning
confidence: 99%
“…Circadian adaptation to night shift work was associated with better performance, alertness, mood, and more sleep (Boudreau et al ., 2013). Adaptation was also demonstrated in increasing and later decreasing cortisol awakening response in young novice police officers between 4 and 14 months after beginning rotating shift work (Lammers-van der Holst and Kerkhof, 2015a) Physicians should be attentive to possible sleep disorders in shiftworking police officers and health promotion programs should attempt to reduce chronic stress (Garbarino, De Carli, Nobili, Mascialino, Squarcia, Penco, Beelke, and Ferrillo, 2002; Gerber et al ., 2010). Fatigue management programs should include education, screening for sleep disorders, and interventions on health consequences (Barger et al ., 2009).…”
Section: Work Schedulesmentioning
confidence: 99%